Hypertension Education and Provision of Self-Service Blood Pressure Monitoring Stations - Agus Priyanto; Dimas Aulia Savitri; Vivin Puji Astutik; Zuryati Zuryati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Hypertension is a non-communicable disease with an increasing prevalence and remains a major risk factor for cardiovascular diseases. Low public awareness of routine blood pressure monitoring leads to many undetected cases of hypertension. This community service activity aimed to improve community knowledge and skills in independently measuring blood pressure through hypertension education and digital blood pressure monitor training. The activity was conducted in Bandung Village, Konang District, Bangkalan Regency, involving 43 participants consisting of adults and elderly residents. The methods included lectures, question-and-answer discussions, demonstrations, simulation of blood pressure monitor use, and the establishment of an Independent Blood Pressure Post. The results showed that before the training, some participants did not fully understand the correct use of the blood pressure monitor. After education and simulation, all participants were able to independently perform blood pressure measurements correctly. This activity proved effective in improving community knowledge and skills as an early detection and prevention effort for hypertension complications.